N-(5-Methylsulfanyl-1,3,4-thiadiazol-2-yl)acetamide - Zhang, Guo-Ying (International Union of Crystallography, 2009)
In the title compound, C(5)H(7)N(3)OS(2), inversion dimers linked by pairs of N—H⋯N hydrogen bonds occur, forming R (2) (2)(8) ring motifs. These dimers are arranged into chains via intermolecular C—H⋯O hydrogen bonds between the methylsulfanyl groups and the O atoms of the carbonyl groups. The acetamido-1,3,4-thiodiazole unit is essentially planar [r.m.s. deviation 0.045 (8) Å].